Fans club brand relationship: Football passion - Cayolla, Ricardo (2021)
Football fans are consumers with a special behaviour with their football club brand. Football is the most popular sport in the world. Demographically, organisations worldwide are becoming increasingly homogeneous. The main aim of this study is to explore why football fans are willing to do some kind of sacrifices in order to continue their relationship with their preferred club brand. Therefore, 97 telephone interviews (from a list of 123 potential respondents) were conducted with entrepreneurs, managers, students, lawyers, retired, employees (public and private), professors, athletes, coach. Participants were contacted in accordance with the procedures of snowball sampling type starting with finding the perpetrators of personal contacts that fit the profile request for the study: the main criterion of the integral elements of this first study is to be people who really like football, people who have the willingness to make sacrifices for the sake of their relationship with the football club brand and team. The findings of the first study reveal four major facets: passion/soul, be different, leave all behind, personal risk. The study contributes to knowledge in marketing field, as well as provides insights to brand managers.